2021
DOI: 10.3390/ijms23010031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aluminium Contamination on the Nervous System of Freshwater Aquatic Vertebrates: A Review

Abstract: Aluminium (Al) is the most common natural metallic element in the Earth’s crust. It is released into the environment through natural processes and human activities and accumulates in aquatic environments. This review compiles scientific data on the neurotoxicity of aluminium contamination on the nervous system of aquatic organisms. More precisely, it helps identify biomarkers of aluminium exposure for aquatic environment biomonitoring in freshwater aquatic vertebrates. Al is neurotoxic and accumulates in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 94 publications
(172 reference statements)
0
5
0
Order By: Relevance
“…8 , also a hallmark in AD. In fish, AChE activity is essential for muscle function and behaviour [ 38 ]. This study examined the effects of AlCl 3 exposure of AChE activity on whole zebrafish embryos (Fig.…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
“…8 , also a hallmark in AD. In fish, AChE activity is essential for muscle function and behaviour [ 38 ]. This study examined the effects of AlCl 3 exposure of AChE activity on whole zebrafish embryos (Fig.…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
“…When it rains, it is easy to wash alum into the canals, so the Fe 2+ and Al 3+ concentration in this area always reaches the highest value compared to the remaining zones. High concentrations of Al 3+ would reduce the number of fish and amphibians due to the reaction of aluminum ions with proteins in the gills and embryos of frogs and also affect birds and other animals that eat fish [31]. As mentioned in the previous section, the water quality monitoring program in the nature reserve was conducted six times per year.…”
Section: Figure 3 Organic Matter Parameters At Functional Zones Of Th...mentioning
confidence: 99%
“…Heavy metals from anthropic activities, such as the steel industry, mining activities, and smelters, are widely found in the environment and cause neurotoxicities ( Squadrone et al, 2013 ; Zhong et al, 2018 ; Jiang et al, 2019 ). It was found that aluminum accumulates in the nervous system of fish and causes damage to nerve tissues, behavior, and cognition ( Closset et al, 2021 ). Silver impairs social preferences, social recognition, learning, and memory in adult zebrafish ( Fu et al, 2021 ).…”
Section: Effects Of Environmental Influences On Behaviormentioning
confidence: 99%